The Analysis of Hoax News Content on Facebook Reviewed from Theory of Critical Discourse Analysis and Linguistic Rules - Muhammad Zulfadhli; Haris Hamdani; Laely Farokhah (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The threat of hoax news on social media makes a news reader more alert. This case encourages someone to increase personal security so that someone is not trapped by leading opinions that are not related to the actual facts. This study aims to describe the analysis of hoax news content on facebook social media in terms of theory of critical discourse analysis and linguistic rules. A qualitative approach with descriptive method was used in this study. The data collection technique used a documentation study on three hoax news content published on facebook. The data analysis technique used triangulation which consisted of data reduction, data presentation, and conclusion drawing and verification. Based on the theory of critical discourse analysis, the results of the study showed that in the representation aspect, hoax news content did not show an appropriate representation between the images presented and the text written on the news. On the aspect of relations, hoax news content did not show an appropriate relationship to the news content. On the aspect of identity, hoax news content does not have a complete identity. In addition, based on the linguistic aspect, in the aspect of word writing, the majority of hoax news content writing used non-standard language. In the element of using capital letters, in hoax news content, it was found that there was an inconsistent use of capital letters. Moreover, on the element of using punctuation, on hoax news content it was found that there were many errors in the use of punctuation. The findings of this study can be used as a reference for news readers to identify news that is classified as hoax or not. Keywords: hoax news, critical discourse analysis, linguistic rules Abstrak Ancaman berita hoaks pada media sosial menjadikan seorang pembaca berita menjadi lebih waspada. Hal ini mendorong seseorang untuk meningkatkan keamanan diri pribadi agar tidak terjebak dengan penggiringan opini yang tidak berkaitan dengan fakta yang sebenarnya. Penelitian ini bertujuan untuk mendeskripsikan analisis konten berita hoaks pada media sosial facebook ditinjau dari teori critical discourse analysis dan kaidah kebahasaan. Pendekatan kualitatif dengan metode deskriptif digunakan pada penelitian ini. Adapun teknik pengumpulan data menggunakan studi dokumentasi pada tiga buah konten berita hoaks yang dipublikasikan di facebook. Teknik analisis data menggunakan triangulasi yang terdiri dari tahap reduksi data, penyajian data, serta penarikan simpulan dan verifikasi. Ditinjau dari Critical Discourse Analysis, hasil penelitian menunjukkan pada aspek representasi, konten berita hoaks tidak menunjukkan representasi yang sesuai antara gambar yang disajikan dengan teks yang ditulis pada berita tersebut. Pada aspek relasi, konten berita hoaks tidak menunjukkan relasi yang sesuai pada isi berita. Adapun pada aspek identitas, konten berita hoaks tidak memiliki identitas yang lengkap. Selain itu, jika ditinjau dari aspek kebahasaan, pada aspek penulisan kata, penulisan konten berita hoaks mayoritas menggunakan bahasa yang tidak baku. Pada unsur penggunaan huruf kapital, pada konten berita hoaks ditemukan adanya pemakaian huruf kapital yang tidak konsisten. Adapun pada unsur penggunaan tanda baca, pada konten berita hoaks ditemukan terdapat banyak kesalahan pada pemakaian tanda baca. Temuan penelitian ini dapat menjadi rujukan bagi pembaca berita untuk mengidentifikasi sebuah berita yang termasuk ke dalam berita hoaks maupun bukan. Kata kunci: berita hoaks, critical discourse analysis, kaidah kebahasaan